Assessment of the utility of the 2‐µ thulium laser in surgical removal of intracranial meningiomas1. Issue 3 (4th March 2013) - Passacantilli, Emiliano; Anichini, Giulio; Lapadula, Gennaro; Salvati, Maurizio; Lenzi, Jacopo; Santoro, Antonio
Abstract Background and Objective Since the 1960s, lasers have been used in neurosurgery for surgical removal of intracranial tumors. Because of its limited penetration (2 mm) through tissues and its wavelength, which is useful in water medium, the 2‐µ thulium laser has been applied primarily in urology. Its features are attractive for application under microscope magnification during neurosurgical procedures. The aim of this study was to evaluate the usefulness of the 2‐µ thulium laser during microsurgical removal of intracranial meningiomas. Materials and Methods Twenty patients with a diagnosis of intracranial meningiomas were treated with surgical intervention using a 2‐µ thulium laser together with bipolar forceps, cavitron ultrasonic surgical aspirator (CUSA) and traditional microdissection instruments. Surgical removal was divided in four phases: (1) dissection from the external structures; (2) coagulation and debulking; (3) dissection from the deep structures; and (4) coagulation and removal of the basal implant. During all these steps, we evaluated the percentage of usage of the 2‐µ thulium laser comparing them with bipolar forceps and ultrasonic aspirator and blunt dissection. Results Thulium laser was used mainly during phases 2 and 4 for 43% and 48.7% of the total removal, respectively. Although also useful during phases 1 and 3, it was only used for 2.2% and 31.3%, respectively: traditional dissection with scissors and forceps was preferred. Conclusions Thulium laser seems to be a useful aid in the surgery of intracranial meningiomas, especially to debulk, shrink, and coagulate the mass and the basal implant. Lasers Surg. Med. 45: 148–154, 2013. © 2013 Wiley Periodicals, Inc.